Protocol-dependent frictional granular jamming simulations: cyclical, compression, and expansion - Santos, A. P.; Srivastava, Ishan; Silbert, Leonardo E.; Lechman, Jeremy B.; Grest, Gary S. (Frontiers in Soft Matter, 2024)
Granular matter takes many paths to pack in natural and industrial processes. The path influences the packing microstructure, particularly for frictional grains. We perform discrete element modeling simulations of different paths to construct packings of frictional spheres. Specifically, we explore four stress-controlled protocols implementing packing expansions and compressions in various combinations thereof. We characterize the eventual packed states through their dependence of packing fraction and coordination number on packing pressure, identifying non-monotonicities with pressure that correlate with the fraction of frictional contacts. These stress-controlled, bulklike particle simulations access very low-pressure packings, namely the marginally stable limit, and demonstrate the strong protocol dependence of frictional granular matter.